(untitled) - Sayer, Jeffrey (Cambridge, UK, 2003)
Science faces major challenges in tackling the interlinked problems of poverty and environmental sustainability. This book investigates these challenges and calls for a restructuring of our present arrangements to achieve integrated natural resource management--integration across scales, system components, disciplines and knowledge types. The new approach advocated requires modelling, multi-scale analysis and action research, institutional and organisational development, and negotiated indicators to improve learning of all stakeholders. The book draws on case studies throughout the world, pointing the direction for a new type of science for integrating conservation and development.
Keywords: Natural resources,Sustainable development,Environmental management,Rural development; Management